Globalization of mass media : opportunities and challenges for the South - Mowlana, Hamid (1998)
Examines whether the globalization of media and communication helps developing countries 'leapfrog' into the information age, improve access to technology, speed development, and contribute to global understanding, equality and harmony. Alternatively inquires whether if discredits indigenous cultures, knowledge and experience, undermines national economic and political independence, and generates worse international disparities.